2017
DOI: 10.1212/wnl.0000000000003517
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment improves cognition after stroke

Abstract: TMT was assessed in 82 of 84 patients undergoing thrombectomy and 86 of 87 control patients alive at 3 months and in 71 of 79 patients undergoing thrombectomy and 72 of 78 control patients alive at 1 year. Rates of timely TMT-A completion were similar in both treatment arms, although patients undergoing thrombectomy required less time for TMT-A completion and had higher rates of error-free TMT-A performance. Thrombectomy was also associated with a higher probability of timely TMT-B completion (adjusted odds ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 15 publications
3
30
1
Order By: Relevance
“…Our study found that patients who received mechanical thrombectomy at broadened therapeutic window had better cognitive improvement after AIS in the 90 days follow-up study in the Chinese population for the first time. This result is consistent with that of the previous study, suggesting that mechanical thrombectomy treatment improves cognitive performance after stroke [14]. While, no significant improvement was found in the Hachinski Ischemic Scale, which is the favored clinical tool used for diagnosing vascular dementia.…”
Section: Discussionsupporting
confidence: 92%
“…Our study found that patients who received mechanical thrombectomy at broadened therapeutic window had better cognitive improvement after AIS in the 90 days follow-up study in the Chinese population for the first time. This result is consistent with that of the previous study, suggesting that mechanical thrombectomy treatment improves cognitive performance after stroke [14]. While, no significant improvement was found in the Hachinski Ischemic Scale, which is the favored clinical tool used for diagnosing vascular dementia.…”
Section: Discussionsupporting
confidence: 92%
“…However, coping and other variables related to their adaptation to a diagnosis of stroke have not been studied [ 38 ]. In line with this, we found similar results regarding neurological outcomes and functional capacities to those obtained in the whole population studied in the REVASCAT [ 39 , 40 , 41 ], indicating that the variables analyzed in this study can be generalized to the totality of people with acute ischemic stroke currently treated with the EVT.…”
Section: Discussionsupporting
confidence: 86%
“…This observation adds to the notion that reducing the overall stroke burden such as through systemic thrombolysis or mechanical thrombectomy may reduce the risk for poststroke cognitive impairment. 38,39 In addition to infarct volume, location is another important predictor of outcome as suggested by earlier studies. Infarct in cortical location tend to predict poor outcomes.…”
Section: Discussionmentioning
confidence: 90%